2022
DOI: 10.1093/g3journal/jkac004
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies SNP markers and putative candidate genes for terpene traits important forLeptocybe invasaresistance inEucalyptus grandis

Abstract: Terpenes are an important group of plant specialized metabolites (PSM) influencing, amongst other functions, defence mechanisms against pests. We used a Genome-Wide Association Study (GWAS) to identify single nucleotide polymorphism (SNP) markers and putative candidate genes for terpene traits. We tested 15,387 informative SNP markers derived from genotyping 416 Eucalyptus grandis individuals for association with three terpene traits, 1,8-cineole, γ-terpinene and p-cymene. A Multi-Locus Mixed Model (MLMM) anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…There have been some previous examples pointing to that GGPPS is involved in the genetic regulation of certain traits. One study shown that an SNP associated with p-cymene in Eucalyptus grandis mapped to the gene encoding GGPPS, explaining 3.66% of the phenotypic variation (Mhoswa et al, 2022). However, no further validation was performed in this study.…”
Section: Function Of Vvggpps In Regulating Norisoprenoids Productionmentioning
confidence: 79%
“…There have been some previous examples pointing to that GGPPS is involved in the genetic regulation of certain traits. One study shown that an SNP associated with p-cymene in Eucalyptus grandis mapped to the gene encoding GGPPS, explaining 3.66% of the phenotypic variation (Mhoswa et al, 2022). However, no further validation was performed in this study.…”
Section: Function Of Vvggpps In Regulating Norisoprenoids Productionmentioning
confidence: 79%
“…The variation in terpene traits, such as 1,8-cineole, γ-terpinene, and p-cymene, appears to be in uenced by a combination of loci with both minor and major effects, suggesting an oligogenic or potentially polygenic nature of these traits (Mhoswa et al 2022). In addition, variations in terpene pro les have been observed between resistant and susceptible Eucalyptus genotypes in response to L. invasa oviposition (Oates et al 2015;Naidoo et al 2018).…”
Section: Resultsmentioning
confidence: 99%